A PLANT TRANSFORMATION VECTOR CONTAINING THE GENE dehD FOR THE DEVELOPMENT OF CULTIVARS RESISTANT TO MONOCHLOROACETIC ACID - E. Mohamed; F. A. Rahiman; R. A. Wahab; C. R. C M. Zain; M. A Javed; F. Huyop (Journal of Animal and Plant Sciences, 2016)
A dehalogenase D gene (dehD) capable of degrading monochloroacetic acid (MCA) has been previously isolated from Rhizobium sp. RC1 and characterized. The 804-bp dehD gene was inserted into pCAMBIA under the control of the cauliflower mosaic virus 35S promoter and designated pCAMdehD, with a total size of 10,592 bp. The pCAMdehD was introduced into tobacco (Nicotiana benthamiana) via Agrobacterium-mediated transformation. The integration and expression of dehD in N. benthamiana was confirmed by PCR and reverse transcription PCR, respectively. MCA-resistant transformants were selected in tissue cultures containing 60 µg/L MCA. Analysis of plants using a leaf-painting assay revealed that transgenic N. benthamiana was resistant to4.0 g/L MCAcompared with 2.0 g/L for non-transformed controls. The use of dehD could thus be advantageous for herbicide-resistant plant breeding systems, and it is also a suitable marker gene for plant-transformation studies. To the best of our knowledge, this is the first report detailing transgenic N. benthamiana engineered with dehD from Rhizobium sp. RC1.
Keywords: Binary vector; dehD gene; Herbicide resistant; Monochloroacetic acid; Tobacco